Ars iusphilosophica. Entrevista a Manuel Atienza - Mora-Sifuentes, Francisco M. (2019)
In this interview, the Spanish lawyer, philosopher and writer Manuel Atienza Rodriguez tells us about the most relevant events that have influenced his academic formation. This meeting allows us to discover the dynamic relationship between Atienza and his academic role models, as well as his thoughts regarding contemporary debate topics within the area of philosophy of Law. Throughout the interview, Atienza is willing to reject the traditional paradigms of legal positivism in order to put forward new theories that should guide modern legal practices. In that sense, although he supports the importance of argumentation within the Law, Atienza remarks the importance of the application of a minimum of moral objectivism in our arguments. Finally, Atienza comments on the evolution of Latin American schools and the relevance that he predicts they will have in the future.